Embroidered Fittings — “Middle Class” Jewelry of the Old Russian Time? - Sobolev, Vladislav Yu. (Actual Problems of Theory and History of Art, 2021)
The article is devoted to one of the types of medieval women’s headdress. The details of this type of headdress — sewed silver plagues, were found in excavations of archaeological monuments of the 13th — the end of the 14th centuries. Plaques with floral and/or geometric ornaments were made of thin silver sheet by embossing. Sometimes they have been decorated with glass inserts of different colors. The front side was covered with gold. The matrices for them have been found only in certain cities — large craft centers of Old Russia (Chernigov, Ryazan, ets.). Headdress decorated with such type of plagues was popular on the territory of the entire Old Russian state. Lost plagues have been excavated in cultural layers of many Russian cities. Complete headgears were discovered in the graves in the North-Western and Western regions and in the hoards related to the Tatar campaigns. Similar headdresses were found in burials of the zone of influence of Russian culture (Karelia) and around the Western border of the Old Russian state (Eastern Lithuania, north-eastern Poland, and Moldova). In eastern Lithuania, this type of female headgears continued to exist throughout the 15th century.